2017
DOI: 10.1007/s11538-017-0261-x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Stochastic Temporal Variations in Intratumoral Blood Flow: The Warburg Effect as a Bet Hedging Strategy

Abstract: While most cancers promote ingrowth of host blood vessels, the resulting vascular network usually fails to develop a mature organization, resulting in abnormal vascular dynamics with stochastic variations that include slowing, cessation, and even reversal of flow. Thus, substantial spatial and temporal variations in oxygen concentration are commonly observed in most cancers. Cancer cells, like all living systems, are subject to Darwinian dynamics such that their survival and proliferation are dependent on deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 49 publications
2
36
0
Order By: Relevance
“…Previous empirical and theoretical work has suggested that cycling hypoxia makes it necessary for cancer cells to adapt to fluctuating environmental conditions (Gillies et al, 2018;Amend et al, 2018) and impacts on tumour growth by increasing clonal diversity, promoting metastasis and supporting more plastic phenotypic variants (Cairns et al, 2001;Cairns and Hill, 2004;Louie et al, 2010;Verduzco et al, 2015;Chen et al, 2018;Saxena and Jolly, 2019). In particular, it has been hypothesised that -by analogy with bacterial populations facing unpredictable environmental changes (Kussell and Leibler, 2005;Smits et al, 2006;Veening et al, 2008;Acar et al, 2008;Beaumont et al, 2009;Nichol et al, 2016) -cancer cell populations could utilise risk spreading through stochastic phenotype switching, which is also known as bet-hedging (Philippi and Seger, 1989), as an adaptive strategy to survive in the harsh, constantly changing environmental conditions associated with cycling hypoxia (Gravenmier et al, 2018;Gillies et al, 2018).…”
mentioning
confidence: 99%
“…Previous empirical and theoretical work has suggested that cycling hypoxia makes it necessary for cancer cells to adapt to fluctuating environmental conditions (Gillies et al, 2018;Amend et al, 2018) and impacts on tumour growth by increasing clonal diversity, promoting metastasis and supporting more plastic phenotypic variants (Cairns et al, 2001;Cairns and Hill, 2004;Louie et al, 2010;Verduzco et al, 2015;Chen et al, 2018;Saxena and Jolly, 2019). In particular, it has been hypothesised that -by analogy with bacterial populations facing unpredictable environmental changes (Kussell and Leibler, 2005;Smits et al, 2006;Veening et al, 2008;Acar et al, 2008;Beaumont et al, 2009;Nichol et al, 2016) -cancer cell populations could utilise risk spreading through stochastic phenotype switching, which is also known as bet-hedging (Philippi and Seger, 1989), as an adaptive strategy to survive in the harsh, constantly changing environmental conditions associated with cycling hypoxia (Gravenmier et al, 2018;Gillies et al, 2018).…”
mentioning
confidence: 99%
“…These hypotheses have been subsequently supported by experimental studies [20,21]. A more recent model [22] proposed a mechanism for the Warburg effect to arise even in oxygenated tumours, despite the apparent loss of fitness (Fig. 3b).…”
Section: Application Of Models To Predict Tumour Progression and Respmentioning
confidence: 67%
“…Models have enhanced mechanistic insight into tumour progression and metastasis, providing unexpected insights into the role of pH in the microenvironment to facilitate invasion of surrounding tissue (Fig. A more recent model [22] proposed a mechanism for the Warburg effect to arise even in oxygenated tumours, despite the apparent loss of fitness (Fig. The mathematical equations of one such model [20] predicted the existence of a pH gradient from the tumour periphery into healthy tissue, which was hypothesised to induce an acellular gap around the tumour and the remodelling of tissue to facilitate tumour invasion.…”
Section: Application Of Models To Predict Tumour Progression and Respmentioning
confidence: 99%
See 2 more Smart Citations